IL-22 Fate Reporter Reveals Origin and Control of IL-22 Production in Homeostasis and Infection - Helena Ahlfors; Peter J. Morrison; João H. Duarte; Ying Li; Judit Bíró; Mauro Tolaini; Paola Di Meglio; Alexandre J. Potocnik; Brigitta Stockinger (2014)
Abstract IL-22 is a cytokine that regulates tissue homeostasis at barrier surfaces. A variety of IL-22–producing cell types is known, but identification on the single-cell level remains difficult. Therefore, we generated a fate reporter mouse that would allow the identification of IL-22–producing cells and their fate mapping in vivo. To trace IL-22–expressing cells, a sequence encoding Cre recombinase was cloned into the Il22 locus, and IL22Cre mice were crossed with reporter mice expressing enhanced yellow fluorescence protein (eYFP) under control of the endogenous Rosa26 promoter. In IL22CreR26ReYFP mice, the fluorescent reporter permanently labels cells that have switched on Il22 expression, irrespective of cytokine production. Despite a degree of underreporting, eYFP expression was detectable in nonimmune mice and restricted to group 3 innate lymphoid cells (ILC3) in the gut and γδ T cells in skin or lung. Upon skin challenge with imiquimod, eYFP+ γδ and CD4 T cells expanded in the skin. Infection with Citrobacter rodentium initially was controlled by ILC3, followed by expansion of eYFP+ CD4 T cells, which were induced in innate lymphoid follicles in the colon. No eYFP expression was detected in small intestinal Th17 cells, and they did not expand in the immune response. Colonic eYFP+ CD4 T cells exhibited plasticity during infection with expression of additional cytokines, in contrast to ILC3, which remained largely stable. Single-cell quantitative PCR analysis of eYFP+ CD4 T cells confirmed their heterogeneity, suggesting that IL-22 expression is not confined to particular subsets or a dedicated Th22 subset.